Blockade of conditioned taste aversion by scopolamine and N-methyl scopolamine: associative conditioning, not amnesia. - Evenden, J; Lavis, L; Iversen, S (1992)
The anticholinergic, scopolamine, consistently disrupts one-trial passive avoidance conditioning but the effects of such drugs on one-trial conditioned taste aversion (CTA) are variable and contradictory. In the present study, treatment of rats with scopolamine impaired the suppression of sucrose intake by post-ingestion administration of lithium chloride (LiCl) in a two-bottle choice test. A similar effect was obtained by using N-methyl scopolamine which penetrates the brain only to a limited degree on acute administration. The blockade of CTA could be prevented in three ways: (i) by exposing the rats to sucrose only on the training day, (ii) by pre-exposing the rats to both sucrose and scopolamine, and (iii) by using a less palatable sucrose/ascorbate mixture. The results demonstrate that the effect of scopolamine on taste aversion is not mediated by the central nervous system, and can be modified by altering the novelty and relative salience of the taste conditioned stimulus. These experiments suggest that conditioned associations between taste and LiCl, and scopolamine and LiCl may underlie the blockade of CTA by scopolamine.